2014 IEEE/ASME International Conference on Advanced Intelligent Mechatronics 2014
DOI: 10.1109/aim.2014.6878168
|View full text |Cite
|
Sign up to set email alerts
|

Comparative numerical studies of electromechanical finite element vibration power harvester approaches of a piezoelectric unimorph

Abstract: Emerging micro-power harvester research using smart material components shows viable self-powered devices capable of capturing mechanical motion and converting it into useful electrical energy that can be further used to supply electrical voltage into rechargeable power storage via a power management electronic circuit. The micro-power harvesters using piezoelectric materials cover a wide range of applications for powering thin film battery technology and wireless sensor systems that can be used to monitor the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Harvesting ambient vibration energy is an increasingly attractive research area due to the ubiquity of this energy source in everyday life (Beeby et al, 2006; Warman et al, 2013). Of particular interest is harvesting vibration energy from human motion (Saha et al, 2008) for powering portable and remote systems (Pancharoen et al, 2014)…”
Section: Introductionmentioning
confidence: 99%
“…Harvesting ambient vibration energy is an increasingly attractive research area due to the ubiquity of this energy source in everyday life (Beeby et al, 2006; Warman et al, 2013). Of particular interest is harvesting vibration energy from human motion (Saha et al, 2008) for powering portable and remote systems (Pancharoen et al, 2014)…”
Section: Introductionmentioning
confidence: 99%
“…The importance to find the natural frequency is to obtain maximum output. The validation of the model is given in Tables 2 and 3 The MatLab programme is validated with material and geometrical properties of literature paper [3] and [5] and comparison of natural frequencies of unimorph piezoelectric energy harvester beam without tip mass and with tip mass at [4] is shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…Research of piezoelectric elements in energy conversion applications necessitates a thorough understanding of solid mechanics and geometrical shapes [2]. Researchers have focused on analytical and numerical studies of unimorph and bimorph beam which forms the basis for the study of energy harvesting [3][4][5] due to its compatibility and ease of applications. Authors have studied experimentally, the effect of orientation of beam by attaching harvester to human leg and concluded that optimum results are obtained for 70 o orientation of harvester with reference to coordinate system [6].…”
Section: Introductionmentioning
confidence: 99%